ETS STRATEGY (Tufts Archival Research Center, 2007)
Report on environmental tobacco smoke (ETS) strategy outlining objectives concerning the issue of ETS and the public. Explains goals are as follows: to demonstrate that ETS has little risk to the public, to illustrate that the idea of ETS has been manipulated in the political and/or media arena, to establish the CIAR as a first rate research facility testing the quality of air, to promote accommodation of smoking and to show that ventilation can be an adequate solution for poor air quality.